Optimum allocation of capacitor and DG in MV distribution network using PSO and opendss - El Tawil, Naji Ammar Mansour; Sulaiman, Marizan; Shamshiri, Meysam; Ibrahim, Zulkifilie (Asian Research Publishing Network (ARPN), 2019)
The optimum capacitor and distributed generation (DG) allocation in medium voltage (MV) distribution network utilizing particle swarm optimization (PSO) for selecting the optimum size and placement of (DG) units can significantly affect the distribution network. Capacitor installation is a standard method for reactive power compensation within a distribution network. The placement and sizing of the capacitor have been optimized in the distribution network for a number of capacitors with the objective of the voltage profile improvement and power loss minimization. Maximum and minimum bus voltage and possible maximum capacitor size were the constraints of the optimum capacitor and sizing problems, which take into account as a penalty factor (PF) within the objective function (OF) and the allocation of DG units. To solve the obtained OF, PSO and Open DSS engines were used in this research to analyse power flow results that obtained from the standard IEEE14 Bus system. The performance evaluation of PSO model was carried out by showing the results that the PSO algorithm. PSO can obtain the optimal solution of the size and location also find the optimum DG size for the loss minimization and voltage profile improvement compared to the standard case without DG and capacitor compensation. All simulations had been performed using MATLAB software.